Anaerobic co-digestion of chicken manure and microalgae Chlorella sp.: Methane potential, microbial diversity and synergistic impact evaluation. (October 2017) - Li, Ruirui; Duan, Na; Zhang, Yuanhui; Liu, Zhidan; Li, Baoming; Zhang, Dongming; Dong, Taili
Highlights: Performance of co-digestion of chicken manure and Chlorella sp. was examined. Enhanced methane production in co-digestion than that of mono-digestion. Synergy effect achieved maximum improvement of methane yield (31.62 mL⋅g −1  VS). Chlorella sp. cell-breaking pre-treatment did not improve the methane yield. Abstract: Anaerobic digestion (AD) is a promising alternative for livestock manure management. This paper presents the experimental results obtained through a batch experiment by using chicken manure (CM) and microalgae Chlorella sp. as co-substrates. The effect of co-digestion was evaluated by varying CM to Chlorella sp. ratios (0:10, 2:8, 4:6, 6:4, 8:2, 10: 0 based on the volatile solids (VS)). The major objective of this study is to evaluate the feasibility and synergistic impact of co-digestion of CM and Chlorella sp. Enhanced 14.20% and 76.86% methane production than CM and Chlorella sp. mono-digestion respectively was achieved in co-digestion at the ratio 8:2. In addition, the co-digestion at the ratio 8:2 showed significantly higher methane yield than the weighted average of the individual substrates' specific methane yield (WSMY), indicating strong synergy effect. The Illumina Miseq sequencing analysis showed that the AD process suppressed the acetoclastic methanogenesis Methanosaeta content; but partly enhanced hydrogenotrophic methanogenesis Methanosarcina, Methanospirillum and Methanobacterium, which was responsible for the methane production. The pre-treated microalgae was then introduced at the optimal ratio 8:2 to estimate the effect of pre-treatment of microalgae on AD process. However, the pre-treatment exhibited no positive effect.